Community Partnership Program (CPP/PKM) High School Teachers in Bandung City and District in E-Learning Based Data Collection Activities - Saputra, Jusep; Kandaga, Thesa; Nurcahyo, Anggoro Ari (Universitas Pendidikan Ganesha, 2019)
The purpose of the Subject Teachers Consultation (STC/MGMP) will be if the teachers are skilled, accustomed and able to develop various activities that are able to support teacher competencies. One of the activities carried out was to participate in the Community Partnership Program (PKM) program development activities with LPTKs such as Pasundan University. The STC included in the Community Partnership Program (CPP/PKM) is the Bandung and City Mathematics STC. Problems with both partners are: (1) Some teachers do not know SPSS and its benefits in research, (2) Understanding of some teachers in collecting data according to the formulation of research problems is still lacking, (3) Some teachers do not know e-learning applications that use video conference. This problem has an impact on the inhibition of research and an increase in the rank of teachers. Approach methods used to overcome problems with training, mentoring, and mentoring. The two partners' solution-resolution procedures will be carried out by the team as follows: (1) Training, mentoring and mentoring in using SPSS features, (2) Training in using e-learning applications (3) Training, mentoring, and mentoring in collect data according to the formulation of research problems. CPP was attended by 14 Mathematics Teachers from the City of Bandung, and 17 Mathematics Teachers from Bandung Regency who were each from the Bandung City and Regency STC. The first meeting resulted in the following conclusions: (1) The quality of CPP in formulating problems, testing instruments, using SPSS features, and video conferencing conducted was very good, (2) The ability of teachers to understand, master, and train in making either test or non-test research instruments are in a pretty good category, (3) the teacher's ability to input data according to data or the scale of the data is in a good category, (4) The teacher's ability to use video conferencing to get guidance and assistance in doing the work is in good category.